2010
DOI: 10.1007/s11705-010-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of biomaterials by photochemical immobilization and photograft polymerization to improve hemocompatibility

Abstract: Thrombus formation and blood coagulation are serious problems associated with blood contacting products, such as catheters, vascular grafts, artificial hearts, and heart valves. Recent progresses and strategies to improve the hemocompatibility of biomaterials by surface modification using photochemical immobilization and photograft polymerization are reviewed in this paper. Three approaches to modify biomaterial surfaces for improving the hemocompatibility, i.e., bioinert surfaces, immobilization of anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Hemocompatibility is an essential property of biomaterials and can be measured by the interaction between the material and the various blood components, such as blood plasma proteins, erythrocytes, platelets and leukocytes [17]. Lack of hemocompatibility can lead to either rejection and/or loss of function [18] initially through the activation of the blood coagulation cascade followed by initiation of immune responses [19]. Blood reactions occur as a result of the physical and chemical properties of implant surface, therefore tolerance can potentially be achieved by altering the biomaterial surface properties [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hemocompatibility is an essential property of biomaterials and can be measured by the interaction between the material and the various blood components, such as blood plasma proteins, erythrocytes, platelets and leukocytes [17]. Lack of hemocompatibility can lead to either rejection and/or loss of function [18] initially through the activation of the blood coagulation cascade followed by initiation of immune responses [19]. Blood reactions occur as a result of the physical and chemical properties of implant surface, therefore tolerance can potentially be achieved by altering the biomaterial surface properties [20].…”
Section: Introductionmentioning
confidence: 99%
“…This will result in non-adhesion of cells [27]. For the latter case where adherent cells are used, it is reported that the thin layer of arginine-glycine-aspartic acid (RGD) peptide to a maleimide-linked surface has been deposited, which provides enhanced cell adhesion and proliferation properties to the surface of the silicon substrate [28] as shown in the Fig. 4 biomaterials surfaces can lead to the enhanced cell adhesion property.…”
Section: Organic Thin Filmsmentioning
confidence: 99%
“…So the organic thin films play an important role for the biomaterials to impart appropriate host response when implanted. Yakai Feng et al (2010) explained the methods of formation of the layer of organic biomolecules though the photochemical immobilization [30]. For photochemical immobilization, photolinkers are used, which have two types of functional groups in one molecule; one is the thermo-active group, and the other is the photo-active group.…”
Section: Organic Thin Filmsmentioning
confidence: 99%
“…13, 14 It is still a significant challenge to improve the blood compatibility of PCUs. 15 Many approaches have been developed to modify PCU as follows: polyethylene glycol (PEG) modification, 16–18 surface modification by photopolymerization, 19, 20 endothelial cell seeding or tissue engineering, release nitrogen monoxide (NO), 21–23 and covalently bonding special molecular structures. 24–29…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic PEG is usually grafted onto biomaterial surfaces to provide a hemocompatible layer, which reduces the absorption of plasma albumen and red blood cells. 19, 20, 31, 32 We aimed to improve the hemocompatibility of PCU with both PEG and sulfoammonium zwitterion. Herein, two novel methods were designed to graft sulfoammonium zwitterions onto PCU polymer chains using PEG as spacer (Fig.…”
Section: Introductionmentioning
confidence: 99%